2015
DOI: 10.1111/jors.12198
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Access and Exposure to Neighborhood Poverty: Evidence From the Moving to Opportunity Program

Abstract: The geographic determinants of social and economic opportunity have received much scholarly attention. A missing link in this body of research is an emphasis on the range of factors influencing low-income households' exposure to neighborhood poverty over time. This paper examines the dynamics of exposure to neighborhood poverty for Moving to Opportunity (MTO) program participants. Our paper is unique in its emphasis on the role of vehicle access as it shapes exposure to neighborhood poverty. We find that vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…First, because they had a car, their earnings increased, and they could then afford to move. Tracy said, “Once I got the car, then I was able to get my own place because I had a job where I made enough money.” Second, vehicle access eased and expanded interviewees’ housing searches (Dawkins, Jeon, and Pendall 2015; Jeon, Dawkins, and Pendall 2018). For Cheryl, a car meant that she “was able to get around and check out places” in less time and with less hassle than on public transit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, because they had a car, their earnings increased, and they could then afford to move. Tracy said, “Once I got the car, then I was able to get my own place because I had a job where I made enough money.” Second, vehicle access eased and expanded interviewees’ housing searches (Dawkins, Jeon, and Pendall 2015; Jeon, Dawkins, and Pendall 2018). For Cheryl, a car meant that she “was able to get around and check out places” in less time and with less hassle than on public transit.…”
Section: Resultsmentioning
confidence: 99%
“…Access to a car also shapes residential mobility. Several studies using data from the U.S. Department of Housing and Urban Development’s Moving to Opportunity experiment found that access to a car enabled low-income households to move to low-poverty neighborhoods (Blumenberg and Pierce 2017a; Dawkins, Jeon, and Pendall 2015; Jeon, Dawkins, and Pendall 2018), while those without a car faced fewer choices when moving (Rosenblatt and DeLuca 2012). Households facing housing and employment instability have even greater incentives to purchase a car despite the high costs of car ownership (Mullen and Marsden 2018; Mullen, Marsden, and Philips 2020).…”
Section: Car Access and Economic And Social Mobilitymentioning
confidence: 99%
“…These questions have thus far received relatively little attention in the literature and remain largely unanswered (Cascetta et al, 2013;Curl et al, 2015;Fransen et al, 2018). Future studies could investigate, for example, how the association between activity participation levels and perceived and objectively measured accessibility varies across the population and to what extent this variation is affected by the built environment, Moreover, while the academic literature has often recognized that increasing physical mobility and accessibility are cause and effect of social mobility (Chetty et al, 2014;Kaufmann et al, 2004;Kronlid, 2008;Lucas, 2012), only a few studies have developed robust identification strategies to measure how accessibility gains from transport policies have impacted employment and educational outcomes (Cervero et al, 2002;Dawkins et al, 2015;Muralidharan & Prakash, 2017). Implicit in most of this literature, and to some extent in the empirical chapters of this thesis, is this idea that promoting greater access to opportunities for disadvantaged groups will in the long run improve their social and economic outcomes and contribute to reducing inequalities.…”
Section: Future Researchmentioning
confidence: 99%
“…However, the MTO literature found that even when participants are initially required to use their voucher in low-poverty neighbourhoods, many eventually returned to high-poverty neighbourhoods once the requirement had been lifted (Sanbonmatsu et al, 2011). Explanations for the inability to maintain residence in low-poverty neighbourhoods include rising housing costs (Rosenblatt and DeLuca, 2012), a lack of access to vehicle and public transportation (Dawkins et al, 2015; Shroder, 2002) and pre-existing social ties to neighbours and families (De Souza Briggs et al, 2010).…”
Section: Introductionmentioning
confidence: 99%